Demographic and Clinical Features in Patients with Mitral Insufficiency of Ischemic Genesis - S. A. Rudenko; S. V. Potashev; A. V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2020)
Myocardial infarction is often associated with ischemic mitral regurgitation. In most patients, ischemic mitral regurgitation develops gradually due to remodeling of the ischemic myocardium and changes in hemodynamics in the left ventricle. Ischemic mitral regurgitation is associated with heart diseases and mortality and is therefore considered an unfavorable prognostic factor.The aim. To study the features of demographic data and the clinical condition of patients with mitral regurgitation of ischemic genesis.Materials and methods. From January 2012 to December 2019, 292 patients with ischemic mitral insufficiency underwent surgical intervention at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine.Results and Discussion. Among patients with mitral regurgitation of ischemic genesis, the majority are men (78.8%). Women suffer from this pathology much less often (21.2%). The mean age of patients with mitral regurgitation of ischemic genesis was 61.9 ± 8.2 years. The proportion of patients with hypertension was almost half of the total number of patients. Every fourth patient suffered from diabetes mellitus (25.7%). In this group, 64.1% (187) patients had a history of myocardial infarction. The majority of patients, 49.3% (144), sought surgery after the first myocardial infarction, 11.0% (32) – after the second heart attack, and in 11 (3.8%) mitral regurgitation occurred only after the third heart attack. Shortness of breath complaints were reported in 249 (85.3%) patients. In most cases (61.3%), shortness of breath occurred only during exercise. Another 70 (24.0%) patients suffered from it even at rest. In this group, 55.1% of patients were classified as NYHA class III–IV. The functional status of 57 (19.5%) patients was so impaired that they were classified as NYHA class IV; 23.6% (69) of patients suffered from IIb degree, and one patient from III degree chronic circulatory insufficiency.Conclusions. Mitral regurgitation of ischemic genesis occurs more often in men (78.8%) of working age (61.1 ± 8.4 years). It leads to a significant reduction in functional status (55.1% of patients were classified as NYHA class III–IV) and physical activity (53.8%). Among the comorbidities, hypertension (47.3%) and diabetes mellitus (25.7%) are the most common.